'Potatoes Made of Oil': Eugene and Howard Odum and the Origins and Limits of American Agroecology. (1st June 1997) - Madison, Mark Glen
Abstract : Eugene P. Odum (b. 1913) and Howard T. Odum (b.1924) were at the forefront of the 'new ecology' of ecosystems, in the 1950s and 1960s. As part of their programme the Odums were firmly committed to bringing both natural and human ecosystems into accord with the laws of ecoenergetics (the flow of energy through a system). American agriculture struck the Odums as a particularly egregious violator of all the laws of ecoenergetics and hence a dangerous paradigm for world development. By diagramming American agriculture as a simplified circuit of energy inputs and outputs, the Odums concluded that energy subsidies had created a dangerously unstable system. As a remedy they suggested an end to the Green Revolution and a modification of human society so as to better approach the steady-state of a mature natural ecosystem. To achieve their programme goals the Odums needed to enlist the support of their fellow ecologists and the government. In this attempt the Odums were largely unsuccessful, as the ecological community and the US government largely ignored their attempt to reform agriculture. While the Odums' agroecological language and theories have persisted until the present, they have largely been divested of the brothers' broader programme of bringing the entire human ecosystem into accord with natural laws. By re-examining the social and scientific context of the Odums' early agroecology it may be possible to better evaluate agroecology as both a tool and a social programme.